DYNAMICS OF ROMANIA-CHINA BILATERAL TRADE: A COMPREHENSIVE OVERVIEW - Alexandra, Sucea Mihaela- (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This study explores the evolving bilateral trade between Romania and China from the 20th century to the present, highlighting significant growth and strategic economic cooperation despite global challenges. Initially bound by political alliances and mutual reconstruction efforts post-World War II, the relationship deepened with Romania's shift to a market economy and China's opening-up policy. Analysing trade data from 1992 to 2021, the research reveals an increase in trade volume, especially after 2000, with China maintaining a trade surplus. Key traded goods include machinery, electronics, textiles, and natural resources. Despite challenges, such as geopolitical considerations, the trade relationship offers opportunities for further growth and diversification. The study underscores the potential for enhanced cooperation in sectors like energy, agriculture, and technology, pointing to a promising future for bilateral economic ties between Romania and China.